SUPPLY CHAIN MODEL OF A MANUFACTURING ENTERPRISE: MULTI-AGENT APPROACH - Panfilova, Elena; Smirnov, Artem; Misko, Oleg; Karimov, Baurzhan; Prodanova, Natalia (International Journal of Supply Chain Management, 2020)
Abstract? The work aims to develop a supply chain model (SCM) for a production plant with limited supply chains, depending on the enterprise?s orders stock. To identify an agents' cooperation model, dynamic interaction within the stochastic uncertainty in the raw materials supply and orders for finished products was modeled using a multi-agent approach. The cooperation model includes production processes, from the raw materials supply to the release of finished products. It consists of self-sustaining agent blocks describing the state and dynamics of the production system. The SCM considers the influence of suppliers, consumers, and structural components, allowing adequately and promptly respond to disturbing market factors and contribute to organizational and economic stability of the enterprise. The supply chain model is formalized mathematically. It examines agent-related changes based on the strategy for optimizing material flows. The strategy in point involves minimizing deviations from a given assortment structure under certain circumstances.